Clinical Characteristics of Anti-3-Hydroxy-3-Methylglutaryl Coenzyme A Reductase Antibodies in Chinese Patients with Idiopathic Inflammatory Myopathies. - Yongpeng Ge; Xin Lu; Qinglin Peng; Xiaoming Shu; Guochun Wang (PLoS ONE, 2015)
The objective of this study was to detect the prevalence of anti-3-hydroxyl-3- methylglutaryl coenzyme A reductase (anti-HMGCR) antibodies in Chinese patients with idiopathic inflammatory myopathies (IIMs), and to analyze the clinical features of the antibody-positive IIM patients.The presence of anti-HMGCR antibodies was detected in 405 patients with IIMs, 90 healthy controls, and 221 patients with other rheumatic diseases by using an ELISA kit. Clinical data from anti-HMGCR antibody-positive and -negative patients were compared. Long-term follow-up of the anti-HMGCR antibody-positive patients was conducted to evaluate the role of anti-HMGCR antibody in IIM disease prognosis.Of the 405 IIM patients, 22 (5.4%) were found to carry the anti-HMGCR antibody. These IIM patients were predominantly female (73%), and only 3 anti-HMGCR antibody-positive patients with IIM were exposure to statins. Most patients experienced progressive onset, and presented with muscular weakness. Dysphagia was observed in half of the patients (p < 0.01), and 15% of these patients experienced the complication of interstitial lung disease (ILD) (p > 0.05). Mean creatine kinase (CK) levels were higher in antibody-positive patients than in antibody-negative patients (p < 0.05). Muscle biopsies were available from 12 anti-HMGCR antibody-positive patients, eight who experienced myofiber necrosis and showed very little or no evidence of inflammatory cell infiltrates in their muscle biopsies. Of these eleven patients who were followed-up 2.5- to 29-month, 73% experienced improvement after treatment. A cross-sectional study showed that anti-HMGCR antibody levels were significantly associated with CK levels (r = 0.486, p = 0.026) as well as with Myositis Disease Activity Assessment (MYOACT) scores (r = -0.67, p = 0.003) during the initial visit. However, changes in serum anti-HMGCR antibody levels did not correlate with changes in CK levels, Manual Muscle Testing 8 (MMT-8) scores or MYOACT scores in long-term follow-up.The major clinical features of anti-HMGCR antibody-positive Chinese IIM patients were muscle weakness and dysphagia, which were seen in patients with and without statin exposure. This subtype of patients were responsive to immunosuppressive treatment and received good prognoses after treatment, but serum levels of the anti-HMGCR antibody do not correlate with disease activity.